Structural-geometric and functional indicators of the heart in patients with multiple myeloma after anti-tumor treatment and COVID-19 - B. B. Samura; M. O. Panasenko; T. O. Samura; I. V. Chorna (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2025)
Multiple myeloma is a severe hematologic malignancy characterized by aggressive progression. Over the last decade, the introduction of novel targeted therapies has significantly improved treatment outcomes. Despite these advancements, cardiovascular complications following antitumor therapy continue to pose a significant challenge, adversely affecting patient life expectancy.